Association of Neutrophil-to-Lymphocyte Ratio and Platelet-to-Lymphocyte Ratio and Coronary Artery Disease Among the Physicians - Tangjitgamol S; Udayachalerm W; Wanishsawad C; Kaewwanna W; Ativanichayapong N (Dove Medical Press, 2024)
Siriwan Tangjitgamol,1 Wasan Udayachalerm,2 Chad Wanishsawad,2 Watcharagan Kaewwanna,1 Natapon Ativanichayapong1 1Research Center, MedPark Hospital, Bangkok, Thailand; 2Cardiology Center, MedPark Hospital, Bangkok, ThailandCorrespondence: Siriwan Tangjitgamol, Research Center, MedPark Hospital, 333 Rama IV Road, Khlong Toei, Bangkok, Thailand, Tel +662 023 3333, Email siriwanonco@yahoo.comIntroduction: Cardiovascular diseases (CVDs) are major global health problem and are the third leading cause of death in the world. Most studies found the neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) were correlated with myocardial infarction and heart failure. Previous studies reported a higher risk of CVD among physicians but no study concerns NLR and the PLR to predict coronary artery disease (CAD) among the physicians.Purpose: This study aimed to evaluate the role of blood features in the CBC, with a particular focus on NLR and PLR levels, in predicting the presence of CAD.Patients and Methods: Data of Thai physicians who participated in the "Save Doctors' Heart" project which was conducted between February 14 and October 31, 2022, were collected from personal information, work and health habits, physical examination, white blood cell (WBC), laboratory, cardiac testing, and presence of CAD. Prior to studying their association with CAD, optimal values of age and each blood parameter, NLR, and PLR were determined.Results: Of 1161 physicians mean age was 47.7 ± 10.16 years. By cardiac tests, CAD was identified in 11.3%. Significantly higher levels of WBC, neutrophils, NLR, and lower platelets were found in physicians with CAD. Except for lymphocytes and platelets which exhibited a reverse association with CAD, other factors were found as significant risk factors for CAD by univariate analysis. By multivariate analysis, the independent risk factors for CAD in order of their adjusted odds ratio (aOR) were age ≥ 50 years (aOR 9.34), NLR ≥ 1.87 (aOR 2.75), CAC score > 1 (aOR 2.39), and PLR ≥ 161.66 (aOR 2.32).Conclusion: NLR and PLR, older age and CAC score were found as independent factors predicting CAD. The findings of this study could potentially provide valuable insights into the relationship between blood parameters and CAD risk among physicians.Keywords: blood cell count, coronary artery disease, lymphocyte, neutrophil, platelets